Does Intellectual Capital effect Corporate Performance: A Study on Pharmaceutical Companies in India - Shaneeb. P, M. Sumathy, Mohammed Nabeel. K, Sujith .T .S (Mathematical Statistician and Engineering Applications, 2022)
This study examined how intellectual capital (IC) affected the corporate performance of Indian pharmaceutical sector enterprises using Public's Value-added intellectual capital coefficient (VAICTTM) model. To measure a firm's corporate performance, the study employed returns on equity (ROE), productivity (ATO), and profitability (ROA). The top 31 Pharmaceutical firms were chosen for the study based on market capitalization. According to the findings, IC efficiency has no effect on productivity and but a considerable and favorable link with the return on equity (ROE) and return on assets (ROA) profitability of the Indian Pharmaceutical sector. While human capital efficiency (HCE) solely affects all proxies of financial performance. Similarly, capital employed efficiency (CEE) has a substantial effect on all corporate performance measures. Additionally, the study discovered that structural capital efficiency (SCE) had no bearing on the return on assets, Asset turnover ratio and return on equity of the Indian Pharmaceutical sector.